2023
DOI: 10.1038/s41467-023-36298-2
|View full text |Cite
|
Sign up to set email alerts
|

The p97-UBXD8 complex regulates ER-Mitochondria contact sites by altering membrane lipid saturation and composition

Abstract: The intimate association between the endoplasmic reticulum (ER) and mitochondrial membranes at ER-Mitochondria contact sites (ERMCS) is a platform for critical cellular processes, particularly lipid synthesis. How contacts are remodeled and the impact of altered contacts on lipid metabolism remains poorly understood. We show that the p97 AAA-ATPase and its adaptor ubiquitin-X domain adaptor 8 (UBXD8) regulate ERMCS. The p97-UBXD8 complex localizes to contacts and its loss increases contacts in a manner that is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 90 publications
1
9
0
Order By: Relevance
“…One possibility is that mtHSP70 knockdown leads to an alteration in membrane fluidity, compromising the dimerization of the UPR ER sensors. This is further corroborated by recent findings that the knockdown of ER-resident proteins alters the ER membrane lipid content, increasing mitochondria and ER contact through increasing membrane order 26 . Furthermore, alterations in lipid content within the ER membrane have been shown to induce UPR ER in the absence of aberrant proteostasis 27 , providing further evidence that membrane lipid content can directly influence the UPR ER signaling pathways.…”
Section: Resultssupporting
confidence: 81%
“…One possibility is that mtHSP70 knockdown leads to an alteration in membrane fluidity, compromising the dimerization of the UPR ER sensors. This is further corroborated by recent findings that the knockdown of ER-resident proteins alters the ER membrane lipid content, increasing mitochondria and ER contact through increasing membrane order 26 . Furthermore, alterations in lipid content within the ER membrane have been shown to induce UPR ER in the absence of aberrant proteostasis 27 , providing further evidence that membrane lipid content can directly influence the UPR ER signaling pathways.…”
Section: Resultssupporting
confidence: 81%
“…4C–E ). After we had made this discovery (published on bioRxiv in May 2022), an independent study confirmed that FAF2 (UBXD8) localizes to the ER and mitochondria in human cells 47 and a subsequent study suggested that this protein is involved in regulating mitochondria-ER contact sites 48 . These complementary findings showcase the potential of CLASP as a discovery tool that can guide functional follow-up experiments.…”
Section: Resultsmentioning
confidence: 98%
“…The TMT-based proteomics was performed exactly as previously described (Ganji et al, 2023 ). Briefly, 100 μg protein of each sample was obtained by cell lysis in lysis buffer (8 M Urea, 200 mM N-(2-Hydroxyethyl)piperazine-N′-(3-propanesulfonic acid) (EPPS) pH 8.5) followed by reduction using 5 mM tris(2-carboxyethyl)phosphine (TCEP), alkylation with 14 mM iodoacetamide and quenched using 5 mM dithiothreitol.…”
Section: Methodsmentioning
confidence: 99%